Labour market integration of immigrants - Evidence for the German guest workers - Werner Smolny; Alexander Rieber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
During the 1960s and 1970s a large number of immigrants came to Germany as temporary labour migrants. Many of them remained, captured their family and their children entered the labour market since the eighties. Our paper analyses their labour market experience in terms of employment, unemployment and earnings. The recruitment stop induced by the first oil crisis in 1973 allows us to distinguish guest workers, on the one hand, and family members, on the other hand, in a natural experiment setting. The results reveal enormous differences between the groups. Guest workers who came until 1973 differ markedly from those migrants who came later as family members, especially in terms of unemployment. These differences are more pronounced for women than for men. The descendants of the European guest workers are very well integrated into the German labour market which points towards positive long-run effects of the guest worker policy measure. However, the migrants stemming from a different ethnic background face much more difficulties in terms of labour market integration.
Keywords: J15; J21; J61; 330